Mitogenome-based phylogeny of the gastropod order Neomphalida points to multiple habitat shifts and a Pacific origin - Zhang, Lili; Gu, Xinyu; Chen, Chong; He, Xing; Qi, Ying; Sun, Jin (Frontiers in Marine Science, 2024)
Neomphalida is an order of gastropod molluscs with highly diverse morphology and a global distribution across various chemosynthesis-based ecosystems from organic falls to hot vents. The phylogenetic relationships of taxa within this order remain contentious, due to the rarity of material leading to a low taxonomic sampling and few genetic markers. Neomphalida includes three families -Melanodrymiidae, Neomphalidae, and Peltospiridae -and molecular sequences are especially lacking in Melanodrymiidae. Here, we assembled a total of 11 mitogenomes covering these three families and 14 genus-level groups to reconstruct the most complete phylogeny of Neomphalida to date. Our current result recovered the monophyly of three families with maximum support and a likely interfamilial relationship of (Melanodrymiidae + Neomphalidae) + Peltospiridae. These indicate the possibility of habitat shifting from non-chemosynthetic deep sea to hot vent and then to sunken wood, accompanied by elevated mitogenome rearrangements and amino acid substitution rates in Melanodrymiidae. By mapping the species distribution on the phylogeny, our results suggest a Pacific origin of Neomphalida and multiple historical dispersal events of Peltospiridae to the Indian Ocean and at least once to the Atlantic.